The Correlation Between Coconut-Based Food Consumption and Blood Pressure Status of Patients at Sumbersari Health Center in Jember - Prasetyo, Aris; Muhammad, Maulana Sava (Fakultas Kedokteran, Universitas Jember, 2026)
Hypertension is a major risk factor for cardiovascular disease worldwide. Dietary components, including coconut-based foods widely consumed in Indonesia, contain bioactive compounds such as potassium, lauric acid, and flavonoids that may influence blood pressure regulation through antioxidant, anti- inflammatory, and vasodilatory mechanisms. However, clinical evidence at the primary healthcare level remains limited. Objective: This study aimed to determine the relationship between coconut-based foodconsumption and blood pressure status among patients at Sumbersari Primary Health Center, Jember. This observational analytic study utilized a cross-sectional design involving 69 respondents selected via consecutive sampling. Dietary intake was assessed using a Food Frequency Questionnaire (FFQ), and blood pressure was measured directly using a digital sphygmomanometer. Data were analyzed using the Pearson Chi-Square test (α = 0.05). Results: The majority of respondents were young adults with a normal Body Mass Index (BMI) and healthy lifestyle patterns. The bivariate analysis revealed no statistically significant relationship between the total consumption of coconut-based food and blood pressure status p = 0.571. Nevertheless, a descriptive analysis indicated a positive clinical trend, wherein the proportion of hypertension was lower in the moderate and high consumption groups comparedto the low consumption group. This lack of statistical significance is likely attributed to the respondents' optimal health profile, as well as food matrix factors, including high-temperature processing that degrades bioactive compounds and concurrent high sodium intake. Coconut-based food consumption was not significantly associated with blood pressure status in this population. However, the descriptive analysis indicated a positive clinical trend, wherein the proportion of hypertension was lower in the moderate and high consumption groups suggesting potential biological relevance that warrants further investigation in larger and more diverse populations.